Implementasi Permainan Puzzle terhadap Peningkatan Kosakata Bahasa Inggris Anak Usia Dini - Dian Novita; Agus Wilson; Sutrisno Sutrisno (SAP (Susunan Artikel Pendidikan), 2023)
This research is aimed as follows : To get emperical data and analyze the effects of puzzle games on English vocabulary mastery for early age. The research was held at Arfanda Kindergarten , Cipayung East Jakarta, the population of 28 students with a sample that is taken randomly about 14 students. The data collection technique uses classroom action observation with the data analysis technique used is a quantitative, qualitative analysis. Learning method with puzzle games can improve English vocabulary mastery in early childhood (83.3%), this method makes students feel happy while learning, apart from that it is also quite active for student involvement in learning.